2014
DOI: 10.5455/2320-1770.ijrcog20140933
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal birth after cesarean section (VBAC) versus emergency repeat cesarean section at teaching hospitals in India: an ICMR task force study

Abstract: Background: Objective of current study was to study the outcome of trial of vaginal birth after Previous Cesarean Section (PCS) and indications for emergency repeat cesarean section at teaching hospitals in India. Methods: Prospective data was recorded on management practices, associated complications and mortality for a period of 8 months in 2005-2006 at 30 medical colleges/teaching hospitals for delivery. Results: A total of 155863 deliveries occurred during the study duration, there were 28.1% (n=43824) ces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…13 The ICMR task force study from the same 30 institutions carried out in the year 2005-2006 reported the most frequent indication for primary CS to be CPD (52.9%), fetal distress (25.8%), severe PIH/eclampsia (5%). 19 Unnikrishnan et al from Mangalore found "previous caesarean delivery" to be most frequent (32.7%) indication for CS followed by fetal distress (19.6%) and Breech presentation (10.3%). 5 Parity-wise analysis done by them revealed the common indications amongst the primigravidae to be fetal distress (31.1%) followed by Breech (15.2%), failed induction (14.3%) and severe PIH (8.9%).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…13 The ICMR task force study from the same 30 institutions carried out in the year 2005-2006 reported the most frequent indication for primary CS to be CPD (52.9%), fetal distress (25.8%), severe PIH/eclampsia (5%). 19 Unnikrishnan et al from Mangalore found "previous caesarean delivery" to be most frequent (32.7%) indication for CS followed by fetal distress (19.6%) and Breech presentation (10.3%). 5 Parity-wise analysis done by them revealed the common indications amongst the primigravidae to be fetal distress (31.1%) followed by Breech (15.2%), failed induction (14.3%) and severe PIH (8.9%).…”
Section: Resultsmentioning
confidence: 98%
“…The success rate of VBAC reported by the ICMR task force study from teaching institutions in the year 2005-2006 was 62.3%. 19 Caesarean section rate at a population level is an indicator of accessibility, availability and utilization of this facility, and is of use to policymakers as an indicator of maternal/perinatal health. 1,8 At hospital level however, the rates need to be monitored and the WHO recommends the Robson"s ten group classification system for the same.…”
Section: (62)mentioning
confidence: 99%
“…The task force of the Indian Council of Medical Research (ICMR) recognizes that there is a delicate balance of benefits and harms as far as a planned vaginal delivery is concerned in women with previous CS. 14 The task force in its multicentric audit at 30 medical colleges in India concluded that the choice of repeat CS or planned VD in a mother with a scarred uterus is one of the most significant and challenging issues in obstetric practice. 14 This is because of the risk of uterine rupture that comes inherently associated with a trial of labour after caesarean (TOLAC) which is an obstetrician's nightmare.…”
Section: Discussionmentioning
confidence: 99%
“…2 And also, according to National Family Health Survey-4 (NFHS-4) the average rate of CS from 2.9% in 1992, has been increased to 17.2% in 2015 ranging from 5.8% in Nagaland to 58% in Telangana. 11 In the present study, the prevalence of CS rate was found to be 35.9% which is almost identical to ICMR task force study.…”
Section: Discussionmentioning
confidence: 99%